CGIAR GENDER Platform: Evaluation Report - Podems, D.; Stathers, T.; Forsythe, L.; Mbevi, L.; Highet, C.; Sweitzer, E.; Maharjan, S. (2023)
The summative and formative evaluation of the GENDER (Generating Evidence and New Directions for Equitable Results) Platform assessed its progress from January 2020 to October 2022, to document lessons and best practices, to also provide forward-looking recommendations for the newly transitioned CGIAR GENDER Impact Platform. The evaluation was conducted between October 2022 – June 2023 by the external team, which was led by an evaluation expert and comprised of three subject matter experts to specifically address Evidence, Methods, and Alliances modules of the Platform.